A comparative evaluation of OTEC, solar and wind energy based systems for clean hydrogen production. (10th February 2020) - Ishaq, H.; Dincer, I.
Abstract: In this article, three different renewable energy methods are considered with wind, ocean thermal energy conversion (OTEC) and solar energy for clean hydrogen production, and Cu-Cl based thermochemical cycle is incorporated into systems to develop potential applications. In the proposed CuCl cycle configuration, the additional heat offered after the thermolysis reactor is recovered to heat the water before reaching the hydrolysis reactor. In the wind energy based hydrogen production system, the maximum exergy destruction rate is found to be 48.3 kW in the wind turbine. The turbine employed to the ocean thermal energy conversion system is found to be undergoing the highest exergy destruction rate of 143.3 kW. The energy and exergy efficiencies of the solar energy based thermochemical CuCl cycle are found to be 32.7% and 33.2% and the maximum exergy destruction rate of 350.69 kW is offered by the thermolysis reactor. The energetically improved configuration of the thermochemical CuCl cycle displays promising results compared to the earlier studies, such as lower heat requirements and higher efficiencies. The study indicates that there is a value to develop a clean OTEC based hydrogen production system and implement for practical applications. Furthermore, some sensitivity analyses are performed to investigate the performance of each system under different operating parameters and discussed.